THE ROLE OF UTILITARIAN VALUE, HEDONIC VALUE, AND FINANCIAL VALUE IN INFLUENCING INTENTION TO STAY AMONG LUXURY HOTEL CUSTOMERS IN JAKARTA - Tommy Setiawan Ruslim; Morris Hazel; Halim Putera Siswanto (Jurnal Scientia, 2022)
Currently, the hotel industry is experiencing a decrease in the intention to stay due to a decline in tourist numbers as well as the use of technology that changes people's behavior and the spread of hotels that provide a unique staying experience. Thus, it is important to research the intention to stay, because it is in order to increase the customers’ purchases. The purpose of this study was to determine whether: 1) Utilitarian value has a significant effect on intention to stay among 5-star luxury hotel customers; 2) Hedonic value has a significant effect on the intention to stay among 5-star luxury hotel customers; and 3) Financial value has a significant effect on the intention to stay among 5-star luxury hotel customers. Samples were selected using the convenience sampling method with a total sample of 150 respondents among Indonesian customers who have rented and stayed at least once. The results of this study show that the perceived utilitarian value, hedonic value, and financial value can positively affect the intention to stay among the customers of 5-star luxury hotels.